Distribuição espaço-temporal de camarões peneídeos (Crustacea: Decapoda: Dendobranchiata) na plataforma continental de Sergipe - Santos, Rafael de Carvalho (2016)
This study evaluated spatio-temporal distribution of the main species of marine shrimp exploited in the state of Sergipe (Xiphopenaeus kroyeri; Litopenaeus schmitti, and Farfantepenaues subtilis) depending on environmental factors. To do this, the samples were collected monthly from september 2013 to august 2014 in nine seasons according to the local bathymetry, three 15min samples in the depths of 5m, 15m and 30m. The catch of shrimps was performed with the use of a shrimping boat equipped with a doble ring nets. In addition to the biological material at each point were also recorded the following environmental factors: temperature and salinity (surface and bottom), organic matter, sediment texture and rainfall. The shrimps were transported to the laboratory identified the specific level, sexed and measured as the carapace length (CL). Hydrological factors were different when compared over time, the sediment characteristics showed similar results among months. In relation to space, only the bottom salinity and the measure of central tendency (Phi) demonstrated difference. Among the studied species, X. kroyeri was the most abundant, followed by F. subtilis and L. schmitti. There was variation in the temporal distribution of shrimp during the study period, except for F. subtilis. All species demonstrated differences in their spatial distribution, with the highest abundances found in 5m and 15m for X. kroyeri and L. schmitti and 30m to F. subtilis. In reason of the water masses do not show variation in the region, the temporal distribution was best explained in terms of the relations of seasonal cycles of rain or the species life cycle. Regarding space, hydrological factors showed no variation, so the differences in the spatial distribution were better explained due to sediment characteristics with X. kroyeri and L. schmitti associated with finegrained, while F. subtilis was more abundant in regions of coarser grains. Individuals of different reproductive categories showed variations in their abundance. Both individuals with developed gonads and immature individuals were found throughout the year, with the presence of two peaks. Regarding space, individuals with developed gonads were found in greater abundance in the deeper regions, while the immature were more abundant near the shallower areas (5m and 15m), reflecting the life cycle and species occurrence. Regarding the conservation of the species, it can be said that only two species are benefiting the area bounded by IBAMA.